Temporal relationship of suicide-related internet searches and suicide rates in Korea: A prewhitened cross-correlation analysis - Seunghyong Ryu; Honey Kim; Hee-Ju Kang; Ju-Yeon Lee; Jae-Min Kim; Sung-Wan Kim (PLoS ONE, 2026)
Objective Suicide-related internet search patterns may reflect population-level behavioral responses to suicide risk. This study investigated the temporal associations between suicide-related internet search volumes and weekly suicide rates in Korea using rigorous time-series methodologies. Methods Weekly suicide rates and search volumes for 25 suicide-related terms were obtained from national mortality records and Naver DataLab for two distinct periods: 2016–2019 and 2020–2023. Prewhitening was applied to mitigate spurious correlations, followed by cross-correlation analyses to assess temporal relationships at lags ranging from 0 to 8 weeks. Results Searches for “psychiatry” and “workplace stress” demonstrated consistent contemporaneous correlations across both study periods. During the 2020–2023 period, significant contemporaneous associations were also observed for prevention-related terms (e.g., “suicide crisis counseling,” “1577-0199,” “psychological counseling”), “fatigue,” “suicide urges,” and “suicide death benefit.” In contrast, “depression” exhibited a significant association only during the 2016–2019 period. Across all findings, the observed effect sizes were modest. Conclusions Specific internet search terms, particularly those related to suicide prevention resources and occupational stress, exhibit temporal associations with population-level suicide rates. These findings suggest that monitoring online help-seeking behaviors and work-related stressors could serve as useful indicators for public health planning, although further research is required to elucidate underlying mechanisms and determine practical applications.